2022
DOI: 10.1186/s12912-022-00845-x
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in caregivers of community-dwelling individuals with disabilities or chronic conditions. A gender-differentiated analysis in a cross-sectional study

Abstract: Background Most care for people with chronic or disabling conditions living in the community is provided in the family context, and this care is traditionally provided by women. Providing informal care has a negative impact on caregivers’ quality of life, which adds to existing health inequalities associated with gender. The aim of this study was to analyze factors associated with the health-related quality of life of caregivers and to determine their differences in a gender-differentiated anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 43 publications
1
8
0
2
Order By: Relevance
“…Furthermore, it is pointed out that knowing the gender characteristics that exist in informal care, as well as their impact on the health and quality of life of caregivers, must be incorporated into nursing assessments and interventions so that, in an individualized way, they promote improvements in health of caregivers according to their gender ( 26 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is pointed out that knowing the gender characteristics that exist in informal care, as well as their impact on the health and quality of life of caregivers, must be incorporated into nursing assessments and interventions so that, in an individualized way, they promote improvements in health of caregivers according to their gender ( 26 ) .…”
Section: Discussionmentioning
confidence: 99%
“…This study found that female caregivers had poorer quality of life than male caregivers. The literature indicates that female caregivers are more likely to have higher anxiety and depression and lower social support than male caregivers, which negatively impacts their quality of life [ 29 ]. In terms of caregiving approach, male caregivers have a more task-oriented approach to caregiving, while female caregivers use more emotion-oriented coping methods.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that approximately half of older caregivers have pain associated with health-related quality of life 36, 37. Assisting another person while experiencing pain yourself can be stressful and negatively affect quality of life 38. For that reason, it is important that caregivers recognize the effects caregiving may have on their mental and physical health and make time to attend to their own needs.…”
Section: Addressing Biases and Related Challenges In Pain Managementmentioning
confidence: 99%